The Well-Being of New Female Farmers in Japan: A Grounded Theory - Ozawa, Ryoko; Omori, Junko (Journal of Rural Community Nursing Practice, 2024)
Background: New female farmers have difficulty in maintaining their health and adjusting to new lifestyles. There have been few to no studies on the well-being of new female farmers. Removal of all barriers to health equity, such as gender discrimination, is paramount to achieving health and well-being for all. Purpose: In this study, we aimed to clarify the well-being of new female farmers in Japan. Methods: Twenty-one new female farmers aged 25–45 years were included. Data were collected through semi-structured interviews and analyzed using a grounded theory approach. Results: The well-being of the new female farmers was composed of the three concepts representing harmony: “mind and body becoming like that of a farmer,” “building a mutual relationship with the help of predecessors,” and “utilizing nature to protect and convey life.” These concepts were closely linked, and “living proudly as a farmer in the embrace of nature” was derived as a theme of the well-being of new female farmers. Conclusion: New female farmers want to be recognized as farmers by both male farmers and society. These farmers also were attracted to farming by the blessings of nature and the feeling of pride in themselves. Thus, to enhance the well-being of female farmers, it is essential to provide opportunities for them to be acknowledged as farmers and to take pride in their accomplishments alongside their peers.